2019
DOI: 10.1177/0309364618796849
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of knee brace, laterally wedged insoles, and toe-out gait on knee adduction moment and fall risk in moderate medial knee osteoarthritis patients

Abstract: There is a synergistic effect of toe-out when combined with knee brace and laterally wedged insole concurrently in second peak knee adduction moment reduction but with a greater degree of fall risk. Simultaneous use of conservative treatments also decreases comfort level. Clinical relevance Patients with mild and moderate knee osteoarthritis are usually prescribed conservative treatment techniques. This study will provide an insight whether or not a combination of these techniques have a synergistic effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…In KOA groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 28 , 43 , 56 ]; 19 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 22 , 23 , 27 , 30 , 31 , 33 35 , 38 42 , 44 , 45 , 49 , 52 , 53 , 55 ]; eight studies reported the mean BMI of 30–34.9 kg/m 2 (grade I obese) [ 18 , 21 , 24 26 , 32 , 37 , 48 ]; and one study reported a mean BMI ≥35 kg/m 2 [ 51 ] (grade II obese). Seven studies did not report the mean BMI of their participants [ 19 , 29 , 36 , 46 , 47 , 50 , 54 ]. In control groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 44 , 45 , 56 ]; 12 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 18 , 21 , 22 , 25 , 31 , 37 – 41 , 48 , 51 ] and six studies did not report the mean BMI of their control participants [ 19 , 29 , 46 , 47 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In KOA groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 28 , 43 , 56 ]; 19 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 22 , 23 , 27 , 30 , 31 , 33 35 , 38 42 , 44 , 45 , 49 , 52 , 53 , 55 ]; eight studies reported the mean BMI of 30–34.9 kg/m 2 (grade I obese) [ 18 , 21 , 24 26 , 32 , 37 , 48 ]; and one study reported a mean BMI ≥35 kg/m 2 [ 51 ] (grade II obese). Seven studies did not report the mean BMI of their participants [ 19 , 29 , 36 , 46 , 47 , 50 , 54 ]. In control groups, four studies reported a BMI mean of 18.5–24.9 kg/m 2 (normal weight) [ 20 , 44 , 45 , 56 ]; 12 studies reported participants’ mean BMI of 25–29.9 kg/m 2 (overweight) [ 18 , 21 , 22 , 25 , 31 , 37 – 41 , 48 , 51 ] and six studies did not report the mean BMI of their control participants [ 19 , 29 , 46 , 47 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of STROBE criterion met ranged from 42% [ 19 ] to 84% [ 43 ]. Ten studies were categorized as high-quality studies [ 21 , 25 , 27 , 35 , 42 44 , 47 , 53 , 55 ], while 29 studies scored less than 65% in relation to the applicable criteria on the STROBE checklist, and were therefore classified as low-quality studies [ 18 – 20 , 22 24 , 26 , 28 34 , 36 – 41 , 45 , 46 , 48 , 49 , 51 , 52 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations